2015
DOI: 10.1111/1467-8551.12098
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Scenario Planning: An Analysis of Inter‐ and Intra‐organizational Strategizing

Abstract: Strategic activity is often punctuated through the application of strategy tools. Despite widespread use, a lack of understanding exists regarding the impact such tools and their practices have on an organization's strategy process. Of the growing body of research tackling the phenomenon, none appears to extend beyond an intra-organizational setting. Acknowledging the importance of multi-organizational partnerships, particularly in the public sector, in this paper an attempt is made to help fill this void thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 115 publications
2
92
0
5
Order By: Relevance
“…This tool has been developed largely by practitioners and, as such, lacks theoretical aspects (Derbyshire, 2016;Goodwin & Wright, 2001). Bowman (2015) similarly states that "an absence of theoretical belonging has left scenario-based approaches drifting between a multitude of frameworks." Bowman (2015) similarly states that "an absence of theoretical belonging has left scenario-based approaches drifting between a multitude of frameworks."…”
Section: Dimensions Of Scenario Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…This tool has been developed largely by practitioners and, as such, lacks theoretical aspects (Derbyshire, 2016;Goodwin & Wright, 2001). Bowman (2015) similarly states that "an absence of theoretical belonging has left scenario-based approaches drifting between a multitude of frameworks." Bowman (2015) similarly states that "an absence of theoretical belonging has left scenario-based approaches drifting between a multitude of frameworks."…”
Section: Dimensions Of Scenario Planningmentioning
confidence: 99%
“…Furthermore, while indicators of scenario planning have varied widely across approaches, the most cited literature presents scenario planning as a structured and analytical process to create characterization of multiple futures to enable stakeholders to rethink strategic decisions and policies (Bowman, 2015). As such, scenarios are constructed through actors' interpretations of their environment.…”
Section: Dimensions Of Scenario Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The intuitive logics model is a plausibility-based approach that enables participants, usually within a workshop setting, to create narratives describing unfolding causal processes, resulting in a set of distinct, alternative possible future worlds. Its popularity stems from its accessibility, providing a good mix of sophistication and ease of use for both project organizers and process participants (Wright et al 2013, Bowman 2016. Its flexibility also lends itself to a wide range of scenario purposes and allows for easy adaptation to a wide variety of contexts.…”
Section: Decision: Choice Of Scenario Development Methodsmentioning
confidence: 99%
“…Our stakeholders, for instance, indicated that one day for scenario development would be all that it would be reasonable to ask people to commit, a design requirement that runs counter to the sufficient time required for scenarios to prompt deeper reflection and exploration (see also Table 2). This risk is particularly relevant when codesigning scenario-based processes, given the disconnect between typical preferences toward pragmatic and time driven outcomes with a concrete focus versus the embracing of uncertainty and openness for exploration and new ideas through which scenarios are most truly successful (Burt and Chermack 2008, Ramírez and Selin 2014, Vervoort et al 2015, Bowman 2016.…”
Section: Improving the Process Of Codesign: Critical Reflections On Tmentioning
confidence: 99%